2015
DOI: 10.1038/srep12574
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for pollinator cost and farming benefits of neonicotinoid seed coatings on oilseed rape

Abstract: Chronic exposure to neonicotinoid insecticides has been linked to reduced survival of pollinating insects at both the individual and colony level, but so far only experimentally. Analyses of large-scale datasets to investigate the real-world links between the use of neonicotinoids and pollinator mortality are lacking. Moreover, the impacts of neonicotinoid seed coatings in reducing subsequent applications of foliar insecticide sprays and increasing crop yield are not known, despite the supposed benefits of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 53 publications
(65 reference statements)
1
52
0
Order By: Relevance
“…That said, our finding is consistent with previous meta-analyses (Naranjo, 2009; Wolfenbarger et al, 2008) that found a negative effect of pyrethroids on predatory arthropods (versus transgenic Bt varieties) of similar magnitude to the negative effect we found for seed-applied neonicotinoids (versus untreated controls). Pyrethroids are the second most widely used class of insecticides in the world after neonicotinoids (Sparks, 2013), and are important alternatives to seed-applied neonicotinoids in North American and European field crops (Budge et al, 2015; Douglas & Tooker, 2015; Furlan & Kreutzweiser, 2015). Their use is therefore likely to increase if, when, and where neonicotinoid use is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…That said, our finding is consistent with previous meta-analyses (Naranjo, 2009; Wolfenbarger et al, 2008) that found a negative effect of pyrethroids on predatory arthropods (versus transgenic Bt varieties) of similar magnitude to the negative effect we found for seed-applied neonicotinoids (versus untreated controls). Pyrethroids are the second most widely used class of insecticides in the world after neonicotinoids (Sparks, 2013), and are important alternatives to seed-applied neonicotinoids in North American and European field crops (Budge et al, 2015; Douglas & Tooker, 2015; Furlan & Kreutzweiser, 2015). Their use is therefore likely to increase if, when, and where neonicotinoid use is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, little publicly available information has been made available on the time and money spent before and after the neonicotinoid restrictions, and limited research has been done regarding the impact of neonicotinoids on crop yield [8], but see [15,95,96]. According to the average response on this issue, compared with 2013/14 season, agronomists spent more time on inspecting oilseed rape crops for pest damage, farmers spent more money for insecticide purchases, and crop yield would be reduced in 2014/15.…”
Section: Discussionmentioning
confidence: 99%
“…Strongly contrasting views about the risks of using this chemical group in agriculture exist, and little consensus has been reached [10,11], with an ongoing argument in UK between the National Farmers Union (NFU) and government regarding the lifting of the restriction [13]. The neonicotinoid debate has resulted in uncertainties for the future of oilseed rape production and management for UK farmers, in terms of cropping areas, insecticide choices and impact on profits [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Regarding bees, we showed that citizen science programs combining the collection of biological material by a targeted network of citizens and the identification to species level et al 2011; Goulson et al 2015). The national scale often has the advantage of representing both a large scale from an ecological point of view and a policy-relevant scale for the future implementation of conservation measures (Woodcock et al 2014;Budge et al 2015). Citizen science Proportion of semi-natural elements 500 m 0.001 ± 0.003 0.126 0.723 n = 70 collections and df = 1 in all cases.…”
Section: Conservation Implicationsmentioning
confidence: 99%